2018
DOI: 10.5888/pcd15.170397
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Outcomes and Delivery-Related Health Care Utilization and Costs Among Pregnant Women With Multiple Chronic Conditions

Abstract: Our objective was to measure obstetric outcomes and delivery-related health care utilization and costs among pregnant women with multiple chronic conditions. We used 2013–2014 data from the National Inpatient Sample to measure obstetric outcomes and delivery-related health care utilization and costs among women with no chronic conditions, 1 chronic condition, and multiple chronic conditions. Women with multiple chronic conditions were at significantly higher risk than women with 1 chronic condition or no chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 7 publications
2
52
0
1
Order By: Relevance
“…( 36 The prevalence of reproductive-aged women with chronic conditions continues to rise, and pregnant women with multiple chronic conditions are at 276% higher risk of SMM and mortality than women with no chronic conditions. (38) Women with multiple chronic conditions are often older than women with a single chronic condition or no chronic conditions. Noncardiovascular medical conditions accounted for 14.3% of pregnancy-related deaths during the period from 2011 to 2015.…”
Section: Causes Of Maternal Mortality and Morbiditymentioning
confidence: 99%
“…( 36 The prevalence of reproductive-aged women with chronic conditions continues to rise, and pregnant women with multiple chronic conditions are at 276% higher risk of SMM and mortality than women with no chronic conditions. (38) Women with multiple chronic conditions are often older than women with a single chronic condition or no chronic conditions. Noncardiovascular medical conditions accounted for 14.3% of pregnancy-related deaths during the period from 2011 to 2015.…”
Section: Causes Of Maternal Mortality and Morbiditymentioning
confidence: 99%
“…Chronic conditions account for one‐third of maternal deaths nationally . A recent national study using the 2013‐2014 National Inpatient Sample of delivery hospitalizations reported that the rate of SMM and mortality among deliveries with at least one chronic condition was nearly two times the rate of those without chronic conditions . Cesarean birth is associated with maternal morbidity in index and future pregnancies, including postpartum hemorrhage, blood transfusion, hysterectomy due to placental implantation disorders, and maternal ICU admission, and may have some adverse neonatal outcomes …”
Section: Introductionmentioning
confidence: 99%
“…8 A recent national study using the 2013-2014 National Inpatient Sample of delivery hospitalizations reported that the rate of SMM and mortality among deliveries with at least one chronic condition was nearly two times the rate of those without chronic conditions. 9 Cesarean birth is associated with maternal morbidity in index and future pregnancies, including postpartum hemorrhage, blood transfusion, hysterectomy due to placental implantation disorders, and maternal ICU admission, 10 and may have some adverse neonatal outcomes. 7,11 Bateman et al used Medicaid health care use data to develop a maternal comorbidity index, which is a simple measure for summarizing the burden of medical (chronic and behavioral) and obstetric (pregnancy-induced) conditions that can be used in population-level research, for example, epidemiologic, comparative effectiveness, and health services research.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these patients suffer chronic medical conditions that are correlated with adverse pregnancy outcomes. 10,11…”
Section: Methodsmentioning
confidence: 99%
“…Many of these patients suffer chronic medical conditions that are correlated with adverse pregnancy outcomes. 10,11 Beginning in 2010, MWH leadership launched a multi-pronged effort to decrease patient harms and improve outcomes.…”
Section: Health System Obstetrical Servicesmentioning
confidence: 99%